2011
DOI: 10.1080/02786826.2011.560909
|View full text |Cite
|
Sign up to set email alerts
|

The Mobility of Fractal Aggregates: A Review

Abstract: A review of the experimental and theoretical literature describing the mobility of fractal aggregates over the previous three decades is presented. Aggregates are those formed via both diffusion and reaction limited cluster-cluster aggregation processes, DLCA and RLCA, which form aggregates with fractal dimensions and prefactors of ca. 1.78 and 1.3 and 2.1 and 0.94, respectively. Emphasis is placed on DLCA aggregates. The entire Knudsen number range from continuum to free molecular is reviewed. The review find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
306
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(335 citation statements)
references
References 64 publications
28
306
1
Order By: Relevance
“…It can therefore be argued that they share particle properties, such as specific surface area (surface area per mass unit), with the much smaller as-produced particles, which typically contain primary particles with a size of ~10 nm for the aggregates and ~40 nm for the sintered spherical particles. To give an order of magnitude estimate it can be shown that a 2 µm agglomerate formed by diffusion limited cluster aggregation (DCLA) in the continuum regime, with primary particles of 10 nm in diameter, would consist of about 30.000 primary particles (Sorensen 2011). This is most likely an underestimation as our SEM images show particles that appear to be more compact than true DLCA aggregates.…”
Section: As-produced Aggregates Vs Emitted Super-agglomerates -Implimentioning
confidence: 70%
“…It can therefore be argued that they share particle properties, such as specific surface area (surface area per mass unit), with the much smaller as-produced particles, which typically contain primary particles with a size of ~10 nm for the aggregates and ~40 nm for the sintered spherical particles. To give an order of magnitude estimate it can be shown that a 2 µm agglomerate formed by diffusion limited cluster aggregation (DCLA) in the continuum regime, with primary particles of 10 nm in diameter, would consist of about 30.000 primary particles (Sorensen 2011). This is most likely an underestimation as our SEM images show particles that appear to be more compact than true DLCA aggregates.…”
Section: As-produced Aggregates Vs Emitted Super-agglomerates -Implimentioning
confidence: 70%
“…(1) holds for any characteristic size of the clusters, obviously with different values of the prefactor k. Several sizes have been used in the literature, including the hydrodynamic radius, the radius of the smallest sphere encompassing the cluster, the size of smallest box enclosing the cluster, etc. [5,10,11]. The radius of gyration is one of the most commonly used sizes because it is a purely geometrical property of the cluster and can be easily determined by static scattering methods.…”
Section: Introductionmentioning
confidence: 99%
“…In three dimensional, space diffusion-limited cluster aggregation leads to fractal aggregates with a typical value 7,18,19 of D f $ 1.8. The behavior of fractal-like aggregates, and spherical particles of the same mass is different.…”
Section: A Coagulation Kernelmentioning
confidence: 99%
“…20 Transport properties of fractal-like particles in gases differ to that of spheres, i.e., nanoparticle morphology has to be taken into account in addition to their size. 19,20 The diffusion coefficient of fractal-like clusters can be roughly estimated by assuming that Ar atoms collide with the sphere having the effective collision radius of fractal-like clusters, 124326 (2012) from the surrounding Ar gas. In other words, when the size disparity between colliding particles (Ar atom versus cluster) is large the sum of collision radii overestimates the number of collisions.…”
Section: A Coagulation Kernelmentioning
confidence: 99%